ALIH KODE DAN CAMPUR KODE DALAM NOVEL ABOUT YOU KARYA VISYA NABILA : KAJIAN SOSIOLINGUISTIK - Cicik Dwi Nur Atiqoh; Yunita Suryani; Suantoko (Universitas Hamzanwadi, 2026)
This study aims to describe the basic concepts of sociolinguistics with a focus on the phenomenon of code switching and code mixing, as well as its causative factors in the novel About You by Visya Nabila. The approach used is a qualitative descriptive method with samples in the form of dialogue excerpts between characters. The data collection technique is carried out through document analysis or content analysis. The results of the study show that code switching appears in two types, namely internal and external code switching, with the switch from Indonesian to English. Meanwhile, code mixing occurs through the insertion of English elements in the form of words, phrases, and clauses in the character's speech. Factors that cause code switching include speakers, counter-speakers, changes in the situation due to the presence of a third person, change of topics, desire to look modern, and the creation of humor. The factors that cause code mixing are related to the attitude of the speaker and the linguistic background they have. In addition, the results of this study show that the study of code transfer and code mixing in literary works can contribute to the development of sociolinguistic science, especially in understanding the dynamics of language use in multilingual societies, and can be used as a reference in learning Indonesian language and literature to understand the social function of language, cultural identity, and the development of bilingual communication in modern literary works.